Generating a taxonomy for genetic conditions relevant to reproductive planning. Issue 3 (March 2016) - Korngiebel, Diane M.; McMullen, Carmit K.; Amendola, Laura M.; Berg, Jonathan S.; Davis, James V.; Gilmore, Marian J.; Harding, Cary O.; Himes, Patricia; Jarvik, Gail P.; Kauffman, Tia L.; Kennedy, Kathleen A.; Simpson, Dana Kostiner; et al.
Abstract : As genome or exome sequencing (hereafter genome‐scale sequencing) becomes more integrated into standard care, carrier testing is an important possible application. Carrier testing using genome‐scale sequencing can identify a large number of conditions, but choosing which conditions/genes to evaluate as well as which results to disclose can be complicated. Carrier testing generally occurs in the context of reproductive decision‐making and involves patient values in a way that other types of genetic testing may not. The Kaiser Permanente Clinical Sequencing Exploratory Research program is conducting a randomized clinical trial of preconception carrier testing that allows participants to select their preferences for results from among broad descriptive categories rather than selecting individual conditions. This paper describes (1) the criteria developed by the research team, the return of results committee (RORC), and stakeholders for defining the categories; (2) the process of refining the categories based on input from patient focus groups and validation through a patient survey; and (3) how the RORC then assigned specific gene–condition pairs to taxonomy categories being piloted in the trial. The development of four categories (serious, moderate/mild, unpredictable, late onset) for sharing results allows patients to select results based on their values without separately deciding their interest in knowing their carrier status for hundreds of conditions. A fifth category, lifespan limiting, was always shared. The lessons learned may be applicable in other results disclosure situations, such as incidental findings. © 2016 Wiley Periodicals, Inc.